INTEGRATION OF ARTIFICIAL INTELLIGENCE (AI) IN THE STRATEGY, ETHICS, AND EFFECTIVENESS OF CONTEMPORARY DAWAH - Munahar, Munahar; Nuruzzaman, Moh. Agil; Roa'zah, Nandipah Roa'zah; Muazaroh, Muslimatun Diana; Afifah, Diana Elfiyatul; Sukirno, Sukirno; Supeno, Supeno; Laila, Najim Hamidatun Nuril (West Science Islamic Studies, 2025)
The development of artificial intelligence (AI) technology has driven significant transformations in da'wah management. This study aims to comprehensively analyze the innovations, opportunities, ethical challenges, and regulatory implications of AI integration in modern da'wah strategies. Using a systematic literature review method on 28 articles selected from a total of 1,022 publications, this study identified four main focuses: (1) AI innovations in da'wah such as congregational behavior analysis, message personalization, and service automation; (2) strategic opportunities in the form of expanding the reach of da'wah, strengthening moderate Islamic narratives, and increasing two-way interactions through digital technology; (3) ethical challenges and risks including the erosion of religious authority, algorithmic bias, misinformation, data privacy, and the potential for extremist manipulation; and (4) the urgency of regulation and collaboration between ulama, technologists, academics, and the government to ensure AI implementation is in accordance with Islamic values. The results of the study confirm that AI has great potential to revolutionize da'wah, but its implementation must be carried out ethically, directed, and inclusively to avoid digital inequality and the distortion of religious meaning. This research provides a theoretical framework and practical recommendations for the development of AI-based da'wah in the future.